Pembuatan Desain LKS Berbasis Virtual Laboratory Melalui ICT pada Materi Gelombang, Optik, dan Pemanasan Global Kelas XI SMA - Nia Nursurila; Yenni Darvina; Hidayati Hidayati; Masril Masril (Universitas Negeri Padang, 2018)
One of the most important learning tools in 2013 Curriculum to support Basic Competence skill is student’s worksheet But in reality, many schools that have not optimized the lab activities in school because there is no complete student’s worksheet in accordance with the demands of the curriculum. Therefore, the curriculum should be designed in accordance with the demands of 2013 Curriculum. In this case the designed curriculum is in the form of virtual laboratory that are accessed through ICT. The advantages of virtual laboratory-based student’s worksheet can improve the mastery of abstract physical concepts. The purpose of this research is to produce student’s worksheet design based on virtual laboratory through ICT. Research conducted including the type of Research and development (R & D) with the appropriate steps proposed by Sugiyono. The object of the research is student’s worksheet based on virtual laboratory through ICT on wave matter, optics, and global warming of class XI SMA. Based on the analysis of data obtained obtained two research results. First, the design of student’s worksheet based on virtual laboratory. Second, the result of validity for student’s worksheet based on virtual laboratory with result of average validity value is 90,19. This shows that the student’s worksheet based on virtual laboratory through ICT on the material of light and global warming is valid to be used in Physics learning in SMA XI class.